Endobronchial ultrasound‐guided transbronchial cryo‐nodal biopsy: a novel approach for mediastinal lymph node sampling - Gonuguntla, Hari Kishan; Shah, Milap; Gupta, Nitesh; Agrawal, Sumita; Poletti, Venerino; Nacheli, Gustavo Cumbo (Respirology case reports, 2021)
Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) is preferred for evaluating malignant lymph nodes and staging of lung cancer. Nevertheless, larger tissue samples are increasingly needed, particularly for molecular analysis. We describe the feasibility, technical details, and complications of EBUS‐guided transbronchial cryo‐node biopsy (TBCNB) in four patients with mediastinal adenopathy. The samples obtained by EBUS‐TBCNB in all cases were adequate for histopathological examination (HPE) and immunohistochemistry (IHC) staining. In case 1, HPE showed non‐caseating epithelioid granuloma with giant cells and fibrosis consistent with sarcoidosis. Case 2 was diagnosed with adenocarcinoma with positivity for ROS1(D4D6). Case 3 showed features of metastatic adenocarcinoma from the breast (positive for Her2, ER, and GATA3). Case 4 was diagnosed with tuberculosis (necrotizing granuloma in histopathology, stain with Ziehl–Neelsen that showed few rod‐shaped bacilli). Only one patient had minimal bleeding at the puncture site controlled with cold saline. There were no adverse events such as major bleeding, pneumomediastinum, or pneumothorax. We describe the feasibility, technical details, and complications of endobronchial ultrasound‐guided transbronchial cryo‐node biopsy (EBUS‐TBCNB) in four patients with mediastinal adenopathy.